Hemostatic Abnormality of Lymphoid Tumors - Deguchi, Katumi; Suzuki, Hikozi; Wada, Hideo; Shirakawa, Shigeru (Journal of the Japan Society of the Reticuloendothelial System, 1988)
We studied hemostatic parameters in 226 patients with lymphoid tumors and compared them with those in 165 patients with myeloid leukemias, to evaluate the relationship between hemostasis and reticuloendothelial system (RES). The changes of hemostatic parameters during the first inductive chemotherapy were less marked in patients with lymphocytic leukemia and malignant lymphoma than in patients with myeloid leukemias. However, patients with acute lymphocytic leukemia showed significantly lower mean levels of fibrinogen and higher mean levels of FDP during therapy than before it. Disseminated intravascular coagulation (DIC) scores increased in patients with adult T cell leukemia (ATL) during therapy, although they had abnormal values in hemostatic parameters (prekallikrein, antithrombin III, antiplasmin, FDP and fibrinogen) on admission. In a hemostatic study of malignant lymphoma during chemotherapy, the mean DIC score was significantly higher in patients with Hodgkin's disease than in those with non Hodgkin's lymphoma. However, the mean DIC score in non-Hodgkin's lymphoma was higher in the diffuse type than in the follicular type, and increased with the progression of the disease. We also investigated procoagulant and fibrinolytic activities in leukemic cells and lymphoma cells, which comprised over 90% of the pathological cells in peripheral blood, 117 patients. The lysates of leukemic cells from acute promyelocytic leukemia and acute monocytic leukemia contained strong activities of procoagulant and plasminogen activator, whereas lysates from blast crisis of chronic myelocytic leukemia, acute myelomonocytic leukemia and malignant lymphoma were dominant in protease activities such as trypsin, elastase and chymotrypsin. The procoagulant and fibrinolytic activities in patients with DIC were stronger than those in patients without DIC. ATL cell lysates had anticoagulant activity which mainly inhibited activation of prekallikrein. Thus, the alternation of coagulation and fibrinolysis during the inductive chemotherapy for lymphocytic leukemia and malignant lymphoma may be related to the procoagulant and fibrinolytic activities in pathological cells.